Cover Picture: An Overview of Interfacial Radiation Chemistry in Nuclear Technology (Isr. J. Chem. 3/2014). Issue 3 (March 2014) - Jonsson, Mats
<x xml:space="preserve">Abstract</x> The cover picture for this issue on Radiation Chemistry shows the corrosion features of a copper cube exposed to gamma radiation in deionized and deoxygenated water. Copper corrosion is one of the main safety issues currently discussed. Read more in the Review by M. Jonsson on page 292.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>